Law no. 7/2017 amending certain provisions of law no. 121/1982 concerning the importers register = قانون رقم 7 لسنة 2017 بتعديل بعض أحكام القانون رقم 121 لسنة 1982 في شأن سجل المستوردين - Egypt : Ministry of Finance. The Egyptian Customs Authority (2025)
Law no. 7 of the year 2017 amending certain provisions of law no. 121 of the year 1982 concerning the imports register قانون رقم 7 لسنة 2017 بتعديل بعض أحكام القانون رقم 121 لسنة 1982 فى شأن سجل المستوردين